GAMBARAN KUALITAS PEWARNAAN TELUR CACING SOIL TRANSMITTED HELMINTH (STH) PADA FESES MENGGUNAKAN SARI KULIT BUAH NAGA MERAH SEBAGAI PENGGANTI EOSIN 2% - Imaniah, Nuril; Salman, Yuliana; Yahya, Yudi; Hidriya, Hajrah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Intestinal nematodes that often infect humans was soil transmitted helminth (STH) worms. This infection could have diagnosed by microscopic examination used an eosin 2% stained. Red dragon fruit was one typed of fruit that could used as a substitute for eosin 2%, especially for red dragon fruit skin, which was a wasted that is often founded in the surrounded environment. The purpose of this studied was to determine the effectiveness of red dragon fruit peeled as a substitute for eosin 2% for stained positive stools with STH worm eggs. This researched is an experimental studied with a completely randomized design (CRD) used a static group comparison pattern design with 24 experimental units. Red dragon fruit skin extract mixed with distilled watered at different concentrations, namely 1:1, 1:2, 1:3, 1:4, and 1:5, and compared with eosin 2% as a controlled. Inspection of STH is examined using native or direct methods. The results of the study based on the Kruskal–Wallis tested founded differences in the quality of staining at concentrations of 1:2, 1:3, 1:4, and 1:5, with eosin 2% as a controlled, while at a 1:1 concentration there was no significant difference with eosin 2% as a control. Based on these results, it can be concluded that red dragon fruit peeled extract is effective as an alternative dye for examined STH worm eggs at a concentration of 1:1, but the red dragon fruit peel extract dye did not produced a contrasting color liked eosin 2%.